2015
DOI: 10.5433/1679-0359.2015v36n1p353
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo das proporções morfométricas entre garanhões e castrados da raça Campolina

Abstract: ResumoA estreita relação entre as características de exterior e a classificação funcional dos equinos tem contribuído consideravelmente no processo seletivo a partir da identificação de indivíduos morfologicamente superiores, permitindo a eliminação do processo reprodutivo de indivíduos portadores de caracteres indesejáveis. Objetivou-se avaliar as medidas lineares dos garanhões e castrados registrados no livro definitivo da ABCCCampolina, bem como compará-las e determinar as correlações existentes. Para tal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
2
9
0
2
Order By: Relevance
“…A similar result was found in this study in horses of the same breed training for eventing in which correlations (Table 3) were found between withers height and croup height (IrI = 0.622; P = 0.008), withers height and substernal height (IrI = 0.625; P = 0.007), croup height and body length (IrI = 0.718; P = 0.001), and croup height and substernal height (IrI = 0.620; P = 0.008), as well as a trend between withers height and body length (IrI = 0.543; P = 0.024). Corroborating the findings of this study in Brazilian Sport Horses, Lucena et al (2015) found in Campolina horses a correlation (P<0.01) between withers height and croup height (IrI = 0.712 and IrI = 0.908 for geldings and stallions, respectively) and between withers height and body length (IrI = 0.737 and IrI = 0.718 for geldings and stallions, respectively). Correlations were also found between croup height and body length (IrI = 0.718; P = 0.001), croup height and substernal height (IrI = 0.620; P = 0.008), body length and head length (IrI = 0.615; P = 0.009) and width (IrI = 0.693; P = 0.003), and head width and croup height (IrI = 0.610; P = 0.012).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A similar result was found in this study in horses of the same breed training for eventing in which correlations (Table 3) were found between withers height and croup height (IrI = 0.622; P = 0.008), withers height and substernal height (IrI = 0.625; P = 0.007), croup height and body length (IrI = 0.718; P = 0.001), and croup height and substernal height (IrI = 0.620; P = 0.008), as well as a trend between withers height and body length (IrI = 0.543; P = 0.024). Corroborating the findings of this study in Brazilian Sport Horses, Lucena et al (2015) found in Campolina horses a correlation (P<0.01) between withers height and croup height (IrI = 0.712 and IrI = 0.908 for geldings and stallions, respectively) and between withers height and body length (IrI = 0.737 and IrI = 0.718 for geldings and stallions, respectively). Correlations were also found between croup height and body length (IrI = 0.718; P = 0.001), croup height and substernal height (IrI = 0.620; P = 0.008), body length and head length (IrI = 0.615; P = 0.009) and width (IrI = 0.693; P = 0.003), and head width and croup height (IrI = 0.610; P = 0.012).…”
Section: Resultsmentioning
confidence: 67%
“…This feature was also found in Campeiro horses (McManus et al, 2005), in Brazilian Sport Horses and Thoroughbreds (Rezende et al, 2014), in horses from a mounted police squadron (Schade et al, 2015), and in Quarter Horses (Mariz et al, 2015). Lucena et al (2015) stated that the good performance of Marchador horses is influenced by the relation between withers height and croup height. Therefore, it is desirable that Campolina horses have a withers height higher than croup height, in contrast to the Brazilian Sport Horses of this study.…”
Section: Resultsmentioning
confidence: 99%
“…A buffalo cow with large thoracic perimeter has long, separated and well-arched ribs, which provides an ample and deep thorax that facilitates respiratory functions (Lucena et al, 2015). These characteristics are good indicators for growth, adaptability and feed efficiency of animals (Oliveira & Nogueira, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Para verificar o efeito de pelagens sobre medidas lineares de alturas de cernelha (ACER), dorso (ADOR), garupa (AGAR) e costado (ACOS); de comprimentos de cabeça (CCAB), pescoço (CPES), dorso (CDOR), garupa (CGAR), espádua (CESP) e corporal (CCORP); larguras de cabeça (LCAB), peito (LPEI) e garupa (LGAR); e perímetros torácico (PTOR) e de canela (PCAN), com bases anatômicas conforme descrito em Lucena et al (2015) é a matriz correspondente aos efeitos fixos: pelagem, categoria animal (machos e fêmeas), ano de nascimento e idade, sendo esta entre três e quatro anos, entre quatro e cinco anos e animais acima de cinco anos para medidas lineares, acrescidos do efeito do técnico para as pontuações de andamento; é o vetor do efeito aleatório, correspondente à propriedade, o qual seguiu distribuição normal, com média igual a zero; e são as matrizes de incidência ligando observações aos efeitos fixos e aleatórios, respectivamente; é o vetor de resíduos.…”
Section: Methodsunclassified
“…Fontes (1957) e Procópio et al (2003) citaram as mais frequentes, enquanto Berbari Neto (2005) averiguou a distribuição das pelagens e a associação com medidas lineares, apenas para machos registrados em definitivo. Lucena et al (2015) descreveram a influência da pelagem sobre variáveis morfométricas de garanhões e machos castrados da raça Campolina.…”
Section: Introductionunclassified